An Investigation on Processing Characteristics of Gold Ore Samples from Barry Deposit, Quebec - E. Yalcin; S. Kelebek (Canadian Institute of Mining, Metallurgy and Petroleum, 2008)
"Two composite samples of a gold-bearing ore from North Western Quebec (Barry Township) were tested to assess their grindability, recovery by flotation and Knelson concentrator as well as extraction using cyanidation.Work index values (BWi) for two composites were found to be 10.4 and 11.0 kWh/tonne, respectively. Flotation tests involved feed samples for which the particle size ranged from a P80 value of 205 ?m to 53 ?m, which resulted in gold recoveries of 91.8% to 95.8% (at gold grades of 130 to 140 g/tonne). Cyanidation tests indicated gold extraction levels ranging from 94.2 to 97.5%. Higher, recoveries were obtained at finer grind sizes and higher cyanide strengths. However, the grind size had a bigger impact on gold leaching. Gold grade and recoveries obtained with the Knelson concentrator device were lower than those obtained by flotation. Mass recoveries to concentrate products strongly depended on the fluidization pressure used. High gold recoveries can be obtained generally at low water pressures of 3 to 4 psi. Higher water pressures produced more selectivity at the expense of higher gold losses.It can be concluded that the gold ore samples tested have good characteristics due to moderate levels of energy requirement, high gold recoveries and extraction rates attainable.INTRODUCTIONBench scale testing of ore samples is an important step in the long series of metallurgical and economic studies involved in bringing new ore bodies into production (Coleman, 1980). Through a laboratory testing program, the behaviour of an ore in a particular process on a larger scale can be established. In an exploratory manner, this testing can be helpful for classification of ores in terms of “good ore” or “problematic ore” by providing preliminary information on recoverability of target minerals. Potential problems if any can be assessed by further investigation of products (e.g., middlings) obtained as a result of testing. A detailed bench scale experimental program in the metallurgical laboratory can also provide the background work for flowsheet development. Depending on the simplicity or complexity of the ore to be tested and type of details required from a testing program, the amount of samples required in the mineral processing laboratory can vary from several kg to more than one hundred kg depending on how detailed the metallurgical testing program is."